Visitors’ satisfaction at managed tourist attractions in Northern Norway: Do on-site factors matter? - Jensen, Ø.; Li, Y.; Uysal, Muzaffer (Pergamon, 2017)
A plethora of research has studied the antecedents of visitor experience in destinations and tourist attractions. Few studies have systematically analyzed the discriminating effects of different types of on-site factors (presentation platform and support services) on tourist satisfaction at different attraction sites. To fill the gap, the current study examines whether and to what extent it is possible to identify some distinct sub-categories of on-site factors with discriminating effects on visitors’ perceptions and evaluations of the site, while taking into consideration the impact of attraction type and visitor type. The findings of a paper-and-pencil survey among 632 visitors at four attraction sites in Northern Norway suggest that visitor perceptions of presentation platform and support services differ significantly by attraction site and type of visit. Also, technological and oral/traditional presentation platforms have discriminating effects on visitor satisfaction among the four sites. The results offer some new research insights into the role of different presentation tools at visitor attractions. Several important practical implications for attraction managers and marketers to drive visitor satisfaction are also provided.